2014
DOI: 10.1016/j.bbr.2014.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal administration of alpha-synuclein aggregates: a Parkinson's disease model with behavioral and neurochemical correlates

Abstract: Parkinson's disease (PD) is a neurodegenerative disorder in which both alpha-synuclein (α-syn) and dopamine (DA) have a critical role. Our previous studies instigated a novel PD model based on nasal inoculation with α-syn aggregates which expressed parkinsonian-like behavioral and immunological features. The current study in mice substantiated the robustness of the amyloid nasal vector model by examining behavioral consequences with respect to DA-ergic neurochemical corollaries. In vitro generated α-syn oligom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 53 publications
2
26
0
Order By: Relevance
“…αSn monomer concentration is important for its aggregation, where a higher concentration aggregates faster. This is also visible in the table, where αSn incubation is done, either at low concentrations for a longer period (up to 7 days), or at higher concentrations for a shorter time (<24 hrs) . The different conditions result in a heterogeneous group of αSOs.…”
Section: Large Variety Of α‐Synuclein Oligomeric Speciesmentioning
confidence: 81%
See 2 more Smart Citations
“…αSn monomer concentration is important for its aggregation, where a higher concentration aggregates faster. This is also visible in the table, where αSn incubation is done, either at low concentrations for a longer period (up to 7 days), or at higher concentrations for a shorter time (<24 hrs) . The different conditions result in a heterogeneous group of αSOs.…”
Section: Large Variety Of α‐Synuclein Oligomeric Speciesmentioning
confidence: 81%
“…According to the seeding and spreading mechanism hypothesis, (misfolded) αSn is secreted by cells and taken up by neighbouring cells, where it templates the misfolding of cellular monomeric αSn. There is evidence that large elongated αSOs, protofibrils, and sonicated fibrils, are able to function as seeds and spread the pathology ,,. Evidence that smaller spherical αSOs might be involved in spreading and seeding is currently scarce.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, more recently many authors have investigated the effects of DA or L-Dopa intranasally applied [11][12][13][14][15][16][17]. Moreover, the intranasal administration has been used by different authors to test the prion-like spreading of pathological a-synuclein in the brain [18][19][20][21]. In particular, it has been reported that nasal administration of a-syn amyloidogenic species produce dopaminergic but also non-dopaminergic parkinsonian neurochemical alterations as well as behavioral deficits indicated by rigidity and reduced locomotor activity [18][19][20].…”
Section: Introductionmentioning
confidence: 98%
“…Moreover, the intranasal administration has been used by different authors to test the prion-like spreading of pathological a-synuclein in the brain [18][19][20][21]. In particular, it has been reported that nasal administration of a-syn amyloidogenic species produce dopaminergic but also non-dopaminergic parkinsonian neurochemical alterations as well as behavioral deficits indicated by rigidity and reduced locomotor activity [18][19][20]. In this respect, it has been demonstrated that there is a final common pathway linking olfactory neuroepithelial receptor cells with axonal projections of the olfactory bulb and these networks are connected to centrifugal neuronal afferents from the substantia nigra dopamine nuclei [22].…”
Section: Introductionmentioning
confidence: 99%